Epididymis rhabdomyoma: A case report and literature review - Han Yang; Qiu Xue-shan; Li Qing-chang; Han Yu-chen; Lin Xu-yong; Zhang Qing-fu; Wang Jian; Wang En-hua; Li Ze-liang (BMC, 2012)
Abstract Genital rhabdomyoma is very rare tumor that usually occurs in the vulvar of young women. Epididymis rhabdomyoma in a young man is extremely uncommon and has rarely been reported. Here, we report a case of epididymis rhabdomyoma of a 17-year-old man and review the literatures. Virtual slide The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1177628224692794